Pengaruh Fasilitas Belajar Dan Kapasitas Guru Terhadap Pemahaman Akuntansi Dengan ILC Sebagai Variabel Moderasi Pada Smk Akuntansi Bagian Medan Utara - Adi Harianto; Eka Nurmala Sari; Irfan (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The purpose of this study was to determine, test and analyze the effect of learning facilities on accounting understanding at the Accounting Vocational School in North Medan, the effect of teacher capacity on accounting understanding at the Accounting Vocational School in North Medan, Internal Locus of control moderated learning facilities and teacher capacity on accounting understanding at the Accounting Vocational School. in North Medan. This study uses a quantitative associative approach with data collection techniques through library research and questionnaires. The research population is class XI Accounting SMK students in North Medan, totaling 175 students. The data analysis of this research used quantitative data analysis techniques. The statistic used is Structural Equation Model - Partial Least Square (SEM-PLS). Software to process this research data using SmartPLS. The results showed that accounting learning facilities had a effect on accounting understanding. The better the available accounting learning facilities, the more students' understanding of accounting will increase. Teacher capacity has a significant effect on accounting understanding. The higher the level of teacher capacity, the higher the level of accounting ability. Internal Locus Of Control does not moderate the effect of learning facilities and teacher capacity on accounting understanding